Analisis Faktor Yang Berhubungan dengan Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Singotrunan Banyuwangi - Narulita Azizah, Hani; Purnamasari, Desy; Christiana, Indah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
There are still many babies who are given formula milk when they visit the health center, while waiting for action the mothers holding the babies are seen holding pacifiers containing formula milk. Considering the importance of giving exclusive breastfeeding to babies, breast milk should still be given to babies, whether to working mothers or perhaps mothers who are reluctant to give breast milk for certain reasons. The aim of the research is to determine the factors associated with exclusive breastfeeding in the Singotrunan Community Health Center Working Area, Banyuwangi Regency. The research design used was correlational with a cross sectional design. The sample in this study was all mothers who had babies 7-60 months in the working area of the Singotrunan Community Health Center, Banyuwangi Regency, and the sample size was 144 people using consecutive sampling techniques. The research instrument used a questionnaire and then analyzed using the chi square test. The research results showed that there was no relationship between age and exclusive breastfeeding (0.829 > 0.05), there was a relationship between education and exclusive breastfeeding and exclusive breastfeeding (0.473 > 0.05), and there is a relationship between family support and exclusive breastfeeding (0.000 < 0.05). Looking at the results of this research, to increase the success of exclusive breastfeeding, midwives need to open classes for pregnant and breastfeeding mothers so that mothers get used to giving breast milk and the child's growth and development becomes more optimal.